ANALYZING THE STRATEGY OF THE BUDGET PORTRAIT IN INDONESIA - Husnul Hotimah; mia (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2025)
The State Budget (APBN) is the main instrument in planning and managing state finances in Indonesia. The APBN describes the estimated state revenues and expenditures prepared to support fiscal policies and national development goals. This journal aims to provide a comprehensive portrait of the APBN, starting from the definition, structure, function, to the challenges faced in its preparation. In general, the APBN has two main components, namely state revenues and state expenditures, each of which plays a role in driving economic growth and creating equitable development. However, the implementation of the APBN faces a number of challenges, including dependence on tax revenues, frequent budget deficits, debt financing, and development disparities between regions. In recent years, the Indonesian government has attempted to improve the efficiency of APBN management by prioritizing infrastructure development, human resources, and reducing dependence on debt. In addition, transparent financial management based on mature planning is expected to support sustainable economic growth, poverty reduction, and improving people's welfare. Despite various challenges in its implementation, the APBN remains a very important tool in realizing the vision of long-term development and advancing the country's economy